NEW INFORMATION TECHNOLOGIES IN TEACHING METHODS SPETSDYSTSYPLIN FLYING IN HIGH SCHOOL - Смирнова, І. Л. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
This article is devoted to the problem connected with new information technologies into pedagogical process into higher educational establishment. The experience of higher educational establishment of Ukraine discussed at scientific Ukrainian conference of 2000 years is reflected by the author